Литі композиційні матеріали на основі мідних сплавів - Рейнталь, О.О.; Лихошва, В.П.; Тимошенко, А.М.; Клименко, Л.М. (Physico-technological Institute of Metals and Alloys, 2023)
Method of composite material obtaining determines degree of diffusion of the particle-matrix connection strength, nature of particles distribution in the melt, level of mechanical characteristics and properties of the final product. The paper proposes a casting method for obtaining a composite dispersion-reinforced material based on copper and its alloys and dispersed particles of chromium steel using laser radiation to heat them in a gas-powder stream. Methods of powder supply are considered: on the melt surface or through a recessed lance. It is found that when the powder is applied to the melt surface without additional mixing, a very shallow area of suspension is formed near the surface, there is no uniform distribution of inclusions throughout the volume of the ingot. Supply of deep gas powder stream allows to obtain a composite ingot with a uniform distribution of the dispersing phase. Composite microstructure and distribution of introduced steel particles in the volume of ingot were studied. Statistical analysis of dispersed component geometric parameters showed changes nature in their shape and size in the volume of ingot. It is determined that due to combined action of laser radiation and electromagnetic field of induction furnace, the process of globularization of steel particles in copper or bronze melt takes place, which is observed by means of microstructural studies of composite ingot. When comparing the mechanical properties, it was found that the hardness of obtained composite exceeds the hardness of cast steel 09X18 by 1.2 times and 2.6 times the hardness of cast bronze OCS 3-8-6. Tribotechnical characteristics of steel, bronze and composite material differ, especially with increasing load. It is determined that the samples of cast bronze are operational at loads not exceeding 5.1 MPa. Cast steel 09X18 can be used as a wearresistant material at loads not exceeding 10.7 MPa. The composite material at different loads proved its significant advantage and showed that it is able to work under load conditions of 15.3 MPa.